Perished by a Painting (A Lacey Doyle Cozy Mystery-Book 6) - Fiona, Grace (Lukeman Literary, 2020)
"Very entertaining. I highly recommend this book to the permanent library of any reader that appreciates a very well written mystery, with some twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews, Roberto Mattos (regarding Murder in the Manor) PERISHED BY A PAINTING (A LACEY DOYLE COZY MYSTERY-BOOK 6) is book six in a charming new cozy mystery series which begins with MURDER IN THE MANOR (Book #1), a #1 Bestseller with over 100 five-star reviews-and a free download! Lacey Doyle, 39 years old and freshly divorced, has made a drastic change: she has walked away from the fast life of New York City and settled down in the quaint English seaside town of Wilfordshire. Fall has arrived in Wilfordshire, bringing with it Fall festivals of food, charming holidays and refreshing return to simple normalcy. To celebrate their new proposal, Lacey and Tom finally get a romantic countryside trip together, and Lacey is thrilled to stumble upon a rare painting in the most unexpected place-a shack on the side of the road. But Lacey has no idea how rare and valuable his painting actually is. When she finds out the shocking news, she grapples with whether she should return it-when a shocking twist and a dead body put her right in the middle of a crime that she must, with her beloved dog at her side, solve-or else lose all that she has worked for. SILENCED BY A SPELL (Book #7), FRAMED BY A FORGERY (Book #8), and CATASTROPHE IN A CLOISTER (Book #9) are also available for pre-order!
Keywords: Krimi, detektivky